Experimental studies and theoretical analysis of the residual properties of the fire-damaged beam-slab assemblies. (1st December 2022) - Wang, Yong; Liu, Weixin; Huang, Zhaohui; Wang, Gongchen; Gao, WanYang; Wang, Shanshan; Gu, Aolin; Han, Guanxu; Zhang, Yajun; Tian, Haoyu; Huang, Fan
Highlights: Tests were conducted to investigate the residual behaviour of the fire-damaged slab-beam assemblies. The influence of the deflection of the beam, and reinforcement ratio and layout was investigated. Modified ellipse method was proposed to predict the ultimate loads and membrane region of specimens. Abstract: This paper investigated the effect of the vertical deflection of the edge beam on the post-fire residual behaviour of the beam-slab specimens, including three fire-damaged specimens and two reference specimens. The mechanical properties of these specimens were investigated, including the load–deflection curves, concrete and reinforcement strains, cracking patterns and failure modes. In addition, a modified ellipse method was proposed to determine the ultimate loads and tensile membrane action region of beam-slab specimens. Results showed that for the fire-damaged specimens, the concrete crushing at the slab's corner and the reinforcement fracture mainly concentrated at the slab panel, and the load capacities of the specimens were enhanced by the tensile membrane action mechanism of each panel. In contrast, for the reference specimens, the concrete crushing easily appeared at the top surface of the edge beam, and the loads were carried by the flexural mechanism of the edge beam. The proposed ellipse method can accurately determine the residual ultimate loads and the tensile membrane action region of fire-damaged continuous slabs.